The preliminary design of the EDEN ISS Mobile Test Facility - An Antarctic greenhouse - Zabel, Paul; Bamsey, Matthew; Zeidler, Conrad; Vrakking, Vincent; Schubert, Daniel; Romberg, Oliver; Boscheri, Giorgio; Dueck, Tom (2016)
EDEN ISS is a European project to investigate cultivation techniques of plants in space for future bio-regenerative life support systems. The technologies will be tested in a laboratory environment as well as at the highly-isolated German Antarctic Neumayer Station III. A small and mobile container-sized test facility will be built in order to provide realistic mass flow relationships. This paper provides a summary of the activities performed in the early design phase of the project. The design phase started with the kick-off meeting in March 2015 and focused on the requirements definition and design of the greenhouse. The EDEN ISS partners met for a design workshop from September 7th to September 18th, 2015 in the Concurrent Engineering Facility of DLR’s Institute of Space Systems in Bremen, Germany. The purpose of the workshop was the generation of a preliminary design for the Mobile Test Facility. The Mobile Test Facility will be built later in the project and used to conduct an over one year long experiment campaign beginning in December 2017 in Antarctica. During the two week workshop, the consortium members worked on their respective subsystems and on how their systems can be integrated in the overall greenhouse. The design of each subsystem was greatly improved. System budgets (e.g. mass, power) were calculated, engineering drawings created and estimates with respect to inputs and outputs made. A very important step was the consolidation of the system and subsystem requirements. This paper summarizes the results of the design work-shop and describes the preliminary design of the EDEN ISS Mobile Test Facility.